If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(n + 1) = 5n + -3 + -2n Reorder the terms: 3(1 + n) = 5n + -3 + -2n (1 * 3 + n * 3) = 5n + -3 + -2n (3 + 3n) = 5n + -3 + -2n Reorder the terms: 3 + 3n = -3 + 5n + -2n Combine like terms: 5n + -2n = 3n 3 + 3n = -3 + 3n Add '-3n' to each side of the equation. 3 + 3n + -3n = -3 + 3n + -3n Combine like terms: 3n + -3n = 0 3 + 0 = -3 + 3n + -3n 3 = -3 + 3n + -3n Combine like terms: 3n + -3n = 0 3 = -3 + 0 3 = -3 Solving 3 = -3 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 7(4.33)+2= | | 1.7p-3=0.9p+13x | | 0.5(2x-5)=4x-1 | | 5x+2y=3x-y | | 27+x-(3x+47)=x+26-10 | | 27+x-(3x-28)=x+26-10 | | (-2x+4)-(9x+1)= | | 14-9x=62-3x | | 4x+5x-102=69 | | (-8-5)-6-2= | | -5(1-5x)*5(-8x-2)=-4x-8x | | 3s=4r | | -8=4(y-5)-8y | | 0.75w-5=1-0.20w | | 2x+3=64 | | 1/12+9/16= | | 1/12+9/16=x | | 24-5y=14 | | (2z+3)+3(5-3z)= | | 3.6x=48.24 | | 11+3x= | | 4x-29=13+6+2x-18 | | (8x-3)+(-4x+2)= | | -23=3e(-9) | | 3.14-0.45= | | 23=x-6+9+2x-19 | | 3y+6=2x+4 | | 12-(4-3x)=21-(13+7x) | | 10+5x-3y-7x+13+5y= | | 1x+1(4)=3 | | w(4w)=144 | | w(w-4)=144 |